2008
DOI: 10.1080/13814780802436093
|View full text |Cite
|
Sign up to set email alerts
|

Multimorbidity in primary care: Prevalence and trend over the last 20 years

Abstract: The increasing amount of multimorbidity in primary care as well as the increasing number of chronic diseases per patient leads to more complex medical care. The general practitioner needs guidelines focusing on multimorbidity to support this care. The registration of chronic diseases by the general practitioner will become more complex and time-consuming.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

21
341
3
24

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 420 publications
(389 citation statements)
references
References 9 publications
21
341
3
24
Order By: Relevance
“…The results remained when adjusting for age and sex meaning that compositional changes in the samples did not explain the observed time trend. Yet, consistent with previous studies that investigated factors associated to health (Agborsangaya et al 2012;Uijen and van de Lisdonk 2008), our results indicated that female sex, higher age, and low education significantly and independently increased the odds of having complex health problems. If the level of education had not increased as it did between 1992 and 2011, the increase in complex health problems would probably have been greater.…”
Section: Discussionsupporting
confidence: 82%
“…The results remained when adjusting for age and sex meaning that compositional changes in the samples did not explain the observed time trend. Yet, consistent with previous studies that investigated factors associated to health (Agborsangaya et al 2012;Uijen and van de Lisdonk 2008), our results indicated that female sex, higher age, and low education significantly and independently increased the odds of having complex health problems. If the level of education had not increased as it did between 1992 and 2011, the increase in complex health problems would probably have been greater.…”
Section: Discussionsupporting
confidence: 82%
“…Uijen and van de Lisdonk described a doubling prevalence of chronic diseases in the patient files of 10 general practitioners in 1985-2005. 23 Also, the percentage of patients with at least four chronic diseases increased with approximately 300%. Tacken et al reported that the prevalence of chronic pulmonary disease, cardiac disease or diabetes mellitus among patients over 65 years attending a general practitioner increased from 41.8% to 46.8% in 6 years (2003)(2004)(2005)(2006)(2007)(2008)(2009)).…”
Section: Discussionmentioning
confidence: 99%
“…The high prevalence of multimorbidity is predominantly attributed to the growing incidence of chronic conditions (2), coupled with the increasing life-expectancy, and it is without a doubt one of the most significant challenges faced by health care providers and policymakers (3,4). Multimorbidity is associated with increased use of health care services (5), a lower quality of life (6), and a higher risk for premature mortality (7).…”
mentioning
confidence: 99%